A forecasted failure: Intersectionality, COVID-19, and the perfect storm. Issue 5 (19th October 2020) - Theidon, Kimberly
Abstract: This article is one chronicle of a pandemic foretold. The consequences of COVID-19 in the United States were not inevitable, and my goal is to trace the humanly and inhumanely authored trajectory this pandemic has taken. Who could be surprised that the burden of morbidity and mortality would follow the color/class/poverty/gender lines that riddle this society? I begin by considering history — specifically the 1918 flu epidemic — and what public health messages from that pandemic reveal about gender, health behavior, and messaging aimed at men who were resistant to barrier methods of flu prevention. I then consider the politics of disposability. How are certain communities made "unimaginable, " such that their deaths provoke a presidential "it is what it is"? Disposability and the lack of national grieving invites us to consider the drastic interruption in rituals of mourning, and to investigate Donald Trump for crime against humanity.